THE USING OF AERATED LIGHTWEIGHT CONCRETE AS AN ALTERNATIVE SUBSTITUTION FOR SOLID RED BRICK - Paryati, Ninik (RESULTAN : Jurnal Kajian Teknologi, 2011)
Aerated lightweight concrete or called Autoclaved Aerated Concrete, is also one of the alternative substitution material of solid red brick. Aerated lightweight concrete now has been widely marketed in several building materials stores and it is used in the project in Indonesia. Aerated lightweight concrete is a concrete which has a lighter specific gravity than a concrete which is generally made by adding the expandable material to create any cavities within, as thus the weight becomes lighter. Aerated lightweight concrete has two types: the wall panel type and the block type, with varied sizes depending on the manufacturer and type of utility. Aerated lightweight concrete weights around 600 - 1600kg/m3 and it can withstand loads up to ± 1200 psi or ± 84.372kg/cm2. Therefore, it is good for construction, especially for wall-constructing since it reduces the burden which is distributed to the foundation. The installation is faster and precise; hence it will save the time and reduce the cost of repairing